Second bone marrow transplantation into regenerating hematopoiesis enhances reconstitution of immune system - Faltusová, Kateřina; Báječný, Martin; Heizer, Tomáš; Páral, Petr; Chen, Chia-Ling; Szikszai, Katarína; Klener, Pavel; Nečas, Emanuel (Frontiers in Immunology, 2024)
In bone marrow transplantation (BMT), hematopoiesis-reconstituting cells are introduced following myeloablative treatment, which eradicates existing hematopoietic cells and disrupts stroma within the hematopoietic tissue. Both hematopoietic cells and stroma then undergo regeneration. Our study compares the outcomes of a second BMT administered to mice shortly after myeloablative treatment and the first BMT, with those of a second BMT administered to mice experiencing robust hematopoietic regeneration after the initial transplant. We evaluated the efficacy of the second BMT in terms of engraftment efficiency, types of generated blood cells, and longevity of function. Our findings show that regenerating hematopoiesis readily accommodates newly transplanted stem cells, including those endowed with a robust capacity for generating B and T cells. Importantly, our investigation uncovered a window for preferential engraftment of transplanted stem cells coinciding with the resumption of blood cell production. Repeated BMT could intensify hematopoiesis reconstitution and enable therapeutic administration of genetically modified autologous stem cells.